2005
DOI: 10.1517/14656566.6.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine for diverticular disease of the colon – a new role for an old drug

Abstract: Colonic diverticulosis is among the most common diseases of developed countries. Its prevalence is approximately 5 - 10% of the population by age 50, and 30, 50 and 66% of those > 50, > 70 and > 85years of age, respectively. Antibiotics have been successfully used in the treatment of uncomplicated diverticular disease; however, the use of mesalazine (alone or in combination with antibiotics) in treating uncomplicated diverticulitis has been successfully developed in recent years. Indeed, mesalazine (with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…It is thought that the development of diverticulitis is associated with an increase in pro-inflammatory cytokines, such as interleukin-1 (IL-1), tumour necrosis factor a (TNFa) and a decrease in anti-inflammatory cytokines IL-1ra, IL-4, IL-10 and IL-11. 55 In a study of patients with diverticulitis or peritonitis, it was indeed found that patients with diverticulitis had higher expression of cells in the omentum ⁄ blood positive for TNF-a (51% ⁄ 35%), interferon (IFN)-c (47% ⁄ 32%) and IL-2 (33% ⁄ 20%). This was not the case for IL-4 expression (0.8% ⁄ 1.3%).…”
Section: Cytokinesmentioning
confidence: 99%
“…It is thought that the development of diverticulitis is associated with an increase in pro-inflammatory cytokines, such as interleukin-1 (IL-1), tumour necrosis factor a (TNFa) and a decrease in anti-inflammatory cytokines IL-1ra, IL-4, IL-10 and IL-11. 55 In a study of patients with diverticulitis or peritonitis, it was indeed found that patients with diverticulitis had higher expression of cells in the omentum ⁄ blood positive for TNF-a (51% ⁄ 35%), interferon (IFN)-c (47% ⁄ 32%) and IL-2 (33% ⁄ 20%). This was not the case for IL-4 expression (0.8% ⁄ 1.3%).…”
Section: Cytokinesmentioning
confidence: 99%
“…Postulates include mucosal prolapse, relative ischemia, bacterial overgrowth, increased exposure to intraluminal toxins and antigens secondary to fecal stasis [19,20] . Some of these factors are similar to those implicated in the pathogenesis of inflammatory bowel disease (IBD) and this colitis may be considered a 'bridge' disease between classic IBD and diverticulitis [21] . There is also evidence that diverticular disease may be based on a disorder of the enteral nervous system, which may, in turn, be caused by an inflammatory process.…”
Section: Causes and Pathogenesismentioning
confidence: 99%
“…Für den Einsatz von Mesalazin (5-Aminosalicylsäure (5-ASA)) zur Sekundärprophylaxe einer Divertikulitis und der Behandlung der chronischen Divertikelerkrankung gibt es ebenso vereinzelt Studien [44,98,100] [18]. Ein ähnliches Setup hatte eine spanische prospektive Studie mit 176 Patienten [19].…”
Section: Aminosalicylateunclassified
“…Neuere Studien weisen trotz Ermangelung einer systemischen Entzündungsreaktion und fehlenden Entzündungszei-chen in der Bildgebung dennoch lokale Entzündungsreaktio-nen in Form eines leicht erhöhten Calprotectins auf [42,43]. Diese Hypothese der Mikroentzündung wird durch die Symptombesserung einer Langzeittherapie durch antiinflammatorische oder antibiotische Therapie bestätigt [44][45][46][47][48].…”
unclassified